PENGGUNAAN STRATEGI PEMBELAJARAN PEER TUTORING UNTUK MENINGKATKAN KREATIVITAS SISWA DALAM MATA PELAJARAN SENI RUPA KELAS VII SMPN 3 PADANG - Putri Sindi, Dra. Zubaidah, M.Pd. (Serupa The Journal of Art Education, 2019)
The purpose of this research is improve student creativity of fine art major with using Peer Tutoring strategy grade VII-2 SMP Negei 3 Padang. The kind of this researchis is classroom action  research which using Peer Tutoring strategy to grade VII-2 SMP Negeri 3 Padang. This researchimplemented in two cycles. Data collection tool used teacher observation sheet, student observation sheet and the format for evaluating student creativity. Data processed by using  percentage formula . The result of data processed show that there is increase of learning outcomes. Learning outcome in cycle I is 74,6 and cycle II incre ase until 91,6. The acquisition of learningoutcomes showed the significant increase. It can conclude that the using of Peer Tutoring strategy can increase student creativity.Keywords: Learning, Peer Tutoring, Creativity